THE EFFECT OF PROGRESSIVE MUSCLE RELAXATION ON BLOOD GLUCOSE LEVELS AND FATIGUESYMPTOM OF PEOPLE WITH TYPE 2 DIABETES MELLITUS - Antoni, Adi (Universitas Aufa Royhan, 2017)
Progressive Muscle Relaxation (PMR) is a relaxation technique for muscle by tensing or tightening one certain group of muscles and releasing the tense followed by focusing the mind to feel the sensation of relaxing. This research was aimed at observing the effect of PMR on blood glucose levels and fatigue symptom of people with Diabetes Mellitus. Quasi experimental Pretest-Posttest Design with control group was used as the design of this research. The samples were collected by employing consecutive sampling technique with 66 respondents consisting of 33 people in intervention group and the other 33 people in control group. Blood glucose levels observed by random blood glucose and The fatigue symptoms observed in this research were measured by using Piper Fatigue Scale. It was found from the results that there were some significant differences on blood glucose levels and fatigue symptoms before and after giving PMR to both the intervention group witht=19.335, p<0.001; t=43.57, p<0.001; and the control group with t=10.053 , p<0.001; t=1.73, p=0.093. Furthermore, another significant difference was also found between the intervention and control group which was t= -7.505, and p<0.001; t= -30.453, and p<0.001. Finally, it was concluded that PMR was effective to reduce blood glucose levels and fatigue synptoms of people with T2DM.